Model Pendidikan Inklusif Berbasis Authentic Instructional Model Pada Anak Usia Dini - Fuad Aminur Rahman; Acep Awaludin (JECED : Journal of Early Childhood Education and Development, 2020)
Writing articles about the model of inclusive education in early childhood is very necessary This is done to provide references or solutions for schools that provide inclusive education, especially in early childhood education. Therefore here the author is interested in offering a reference or solution about the development of inclusive instructional models based on authentic instructional models in early childhood, namely the inclusive education model that tries to provide an overview in combining the principles of access to education for all students or disadvantaged individuals, and not only for those with special needs. Therefore, the nature of the inclusive education model is a shift from theories, assumptions, practices, and special models of disabilities to the specific non-disability inclusive education system.